Cleaner wrasse Labroides dimidiatus perform above chance in a “matching-to-sample” experiment - Aellen, Mélisande; Siebeck, Ulrike E.; Bshary, Redouan (PloS one, 2022)
Concept learning have been studied widely in non-human animal species within or not an ecological context. Here we tested whether cleaner fish Labroides dimidiatus , which show generalised rule learning in an ecologically relevant context; they generalise that any predator may provide protection from being chased by other fish; can also learn a general concept when presented with abstract cues. We tested for this ability in the matching-to-sample task. In this task, a sample is shown first, and then the subject needs to choose the matching sample over a simultaneously presented different one in order to obtain a food reward. We used the most general form of the task, using each stimulus only once in a total of 200 trials. As a group, the six subjects performed above chance, and four individuals eventually reached learning criteria. However, individual performance was rather unstable, yielding overall only 57% correct choices. These results add to the growing literature that ectotherms show the ability of abstract concept learning, though the lack of stable high performance may indicate quantitative performance differences to endotherms.